PENYULUHAN KESEHATAN MENTAL PADA SANTRI PUTRA DI PONDOK PESANTREN DARUSY SYAHADAH BOYOLALI - Debby Yulianthi Maria; Hodiri Adi Putra; Parmadi Sigit Purnomo (Jurnal Padamu Negeri, 2026)
Health is a basic need for everyone that must be met first to be able to carry out their activities. Mental health is no exception, and it is important to maintain and care for it to prevent events that could damage the soul. Community service activities in the form of health education are one method to increase students' understanding of mental health. Understanding mental health is crucial so that it can be used to control emotions. Adolescence is a stage of growth that is a very sensitive phase in dealing with the problems they face. The target of this community service activity is 62 students who are still studying in high school. The aim is to increase the students' understanding of mental health. The implementation method is carried out face-to-face at the mosque using a lecture, discussion, and question-and-answer model. This is then followed by presentation of material and a question-and-answer discussion, as well as sharing of students' personal experiences. The community service activity has had positive results for the students, with data obtained indicating an increase in understanding, especially regarding mental health. This was evident when the team asked students about the material that had been presented and gave correct answers. The team provided suggestions for maintaining and practicing it to maintain emotional well-being and be able to socialize in daily life. And it is still necessary to provide follow-up activities to be able to provide full awareness and habits in maintaining mental health for students.